Proekologiczne zarządzanie personelem - Zaremba-Warnke, Sabina (Ecological Staff Management, 2008)
The article shows that employees' environmental awareness is the main aim of ecological staff ma-lent. The article presents the analysis of effective rules which are used to build up employees' en-awareness. The article also shows list of good practices in ecological staff management and les of them. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 179-191